Automated Monitoring and Control System of Solar Greenhouse Using ESP32 and Blynk Application - Meridith Lindsey Q. Galon; Michael Vincent R. Tumaliwan; Marianne M. Sejera (Engineering Proceedings)
Greenhouse farming has brought a revolution in agriculture as it provides a climate favorable to crops all year round. Besides securing the production of foods of higher quality, it also extends the growing seasons and protects crops from pests and harsh weather. The greenhouse is centrally controlled by the user due to the technological advancements of devices such as cell phones and a control system of temperature, which is important for the plant. To realize remote real-time automated monitoring of the greenhouse based on the user settings, an Android app was developed in this study.